Pengaruh Modal Intelektual Pada Nilai Perusahaan dengan Kinerja Keuangan Sebagai Variabel Mediasi - Ariyani, Ni Komang Sri; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 25 No 1 (2018)DO - 10.24843/EJA.2018.v25.i01.p18, 2018)
This study aims to test and provide empirical evidence of the influence of intellectual capital on corporate value with financial performance as a mediation variable. Company value is measured by book value (PBV) and company financial performance is measured by return on equity (ROE). This research was conducted at pharmaceutical sub-company listed on BEI year 2012-2016. The number of samples taken as many as 40 companies, with purposive sampling method. Data collection method in this research is non-participant observation. Data analysis technique used is path analysis. The result of the analysis shows that intellectual capital has positive effect on financial performance, intellectual capital has positive effect on firm value, financial performance has positive effect on firm value and test result stated that financial performance is able to mediate relationship between intellectual capital at firm value. Keywords: intellectual capital, firm value, financial performance